2006
DOI: 10.1093/alcalc/agl075
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Societal Level Factors on Men's and Women's Alcohol Consumption and Alcohol Problems

Abstract: Gender differences should be studied not only as individual behaviours, but also as societal traits, associated with other characteristics of the social system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
99
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 17 publications
13
99
0
Order By: Relevance
“…Given the recent narrowing of the gender difference in alcohol consumption, it is posited that the change of women's traditional feminine norms, and increasing endorsement of traditionally masculine traits, may explain converging drinking rates. This notion is supported by international studies that have found that in societies where women achieve greater equality and approach masculine social status, women and men's drinking rates tend to be more similar (Rahav et al, 2006).…”
Section: Gender and Healthmentioning
confidence: 84%
See 3 more Smart Citations
“…Given the recent narrowing of the gender difference in alcohol consumption, it is posited that the change of women's traditional feminine norms, and increasing endorsement of traditionally masculine traits, may explain converging drinking rates. This notion is supported by international studies that have found that in societies where women achieve greater equality and approach masculine social status, women and men's drinking rates tend to be more similar (Rahav et al, 2006).…”
Section: Gender and Healthmentioning
confidence: 84%
“…Studies sampling drinking rates internationally have found similar results, indicating that cross-culturally, men drink at higher rates than women (Wilsnack et al, 2009;Rahav et al, 2006). Wilsnack and colleagues (2009) argue that women drink less frequently for a number of reasons, including: women generally are lighter drinkers than men, drinking is not as significant for women's social roles as it is for men's, and because women may stop drinking during pregnancy and child-rearing, and then may not resume drinking.…”
Section: Outcomes: Alcohol Use and Alcohol-related Problemsmentioning
confidence: 85%
See 2 more Smart Citations
“…Drinking is a gendered activity, with men drinking more often and more heavily than women internationally (Rahav et al 2006), and traditionally expected to drink (primarily beer) excessively and in public (Lemle and Mishkind 1989). We enact varied gender identities by taking part in behaviour that has cultural meanings that are associated with versions of masculinity and femininity , Lyons 2009); here gender is an ongoing bodily performance (Butler 1993).…”
Section: Introductionmentioning
confidence: 99%